2011
DOI: 10.1017/s0022112010004866
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of heat transfer from the stagnation region of a heated cylinder affected by an impinging wake

Abstract: The effect of an incoming wake on the flow around and heat transfer from the stagnation region of a circular cylinder was studied using direct numerical simulations (DNSs). Four simulations were carried out at a Reynolds number (based on freestream velocity and cylinder diameter D) of Re D = 13 200: one two-dimensional (baseline) simulation and three three-dimensional simulations. The three-dimensional simulations comprised a baseline simulation with a uniform incoming velocity field, a simulation in which rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Numerical studies also have painted a better picture of this mechanism. For example, the DNS studies of Wissink & Rodi (2006), Wissink & Rodi (2009, 2011a showed that the increase in heat transfer occurs through an up-wash of hot fluid away from the cylinder and a down-wash of cold fluid towards the cylinder. The LES studies of Xiong & Lele (2007) and Bhaskaran & Lele (2010) observed longitudinal stream-wise vortical structures that increase heat transfer by being stretched along the surface of the turbine blade.…”
Section: Mechanism Of Heat Transfer Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical studies also have painted a better picture of this mechanism. For example, the DNS studies of Wissink & Rodi (2006), Wissink & Rodi (2009, 2011a showed that the increase in heat transfer occurs through an up-wash of hot fluid away from the cylinder and a down-wash of cold fluid towards the cylinder. The LES studies of Xiong & Lele (2007) and Bhaskaran & Lele (2010) observed longitudinal stream-wise vortical structures that increase heat transfer by being stretched along the surface of the turbine blade.…”
Section: Mechanism Of Heat Transfer Enhancementmentioning
confidence: 99%
“…Secondly, the spanwise length of the grid-element is larger compared to the standard spanwise size used to compute the flow around a single cylinder. For example, the study of Venema et al (2011) had a spanwise length of 2.5D, while Wissink & Rodi (2011b) and Wissink & Rodi (2011a) had 2D and 0.6D respectively. The presence of the gridelement increases this size by a factor of 7, which in turn increases the number of cells accordingly.…”
Section: Numerical Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Intense quasi-streamwise vortices were found to develop near the leading edge leading to turbulent heat flux to peak much closer to the wall than the Reynolds stresses. Wissink and Rodi [12] performed the first DNS in which the influence of an incoming turbulent wake on stagnation heat transfer from an heated cylinder was studied. A Reynolds number of Re D = 13,200, based on the free-stream velocity and the diameter of the cylinder, was employed.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to refer to this paper for an extensive literature review on laminar heat transfer induced by free stream fluctuations. Compared to Wissink and Rodi [12], the present paper studies the effect of oncoming grid turbulence, rather than turbulence in a wake, on stagnation heat transfer and employs a significantly higher Reynolds number.…”
Section: Introductionmentioning
confidence: 99%